A Lego‐like steel‐framed system for standardization and serial production. Issue 1 (9th February 2023) - Odenbreit, Christoph; Yang, Jie; Romero, Alfredo; Kozma, András
Abstract: A Lego‐like steel‐framed structural system has been developed within the frame of an RFCS project, REDUCE, to facilitate 1) deconstruction of composite structures, 2) circularity at structure and element levels, and 3) serial production in construction by promoting a greater standardization of structural elements. The system utilizes innovative demountable shear connections for composite flooring solutions with precast concrete elements, and adjustable steel connections for use in both beam‐to‐beam and beam‐to‐column connections. The first use case of the structural system has been realized in the Petite Maison project which is a demonstration project for circularity and contributes to the event ESCH2022. Each construction element is linked to a digital database and remains available for future reuse, as a result of the plug‐and‐play, demountable and robust features of the developed system. This paper presents the proposed demountable system, the results from experiments and finite element analyses on the behaviour of shear connections, composite beams, and steel connections, and indicates the analysing methods for structural engineers to open a pathway for full implementation of the structures built into digital tools, fabrication, and construction.